Interview for paradox of information / Nor Amirah Mohd Norroe and Nurul Adelina Zainudin - Mohd Norroe, Nor Amirah; Zainudin, Nurul Adelina (Faculty of Information Management, 2015)
Interview with Madam Rafidah binti Abdul Aziz, lecterur of Faculty of Information, UiTM Puncak Perdana.